Heart Disease Prediction By Using Case Based Reasoning (Cbr) - Chan, Hue Wah (2023)
This study provides an overview of heart disease prediction using intelligent system. Disease prediction is an important task in the medical industry. It is hard to get an accurate result by using the traditional method which is doctor’s experience. Therefore, to overcome these issues, the intelligent system will be applied to replace the traditional approach. There are other intelligent system approaches available, but just three will be studied in this study such as Fuzzy Logic, Neural Network, and Cased-Based Reasoning (CBR). The comparison in term of accuracy will be made among the three chosen intelligent system techniques. Next, only the Cased-Based Reasoning (CBR) will be selected to perform the heart disease prediction. During the prediction phase, the heart disease dataset will go through data pre-processing to clean it and data splitting to divide it into training and testing data. Then, the selected intelligent system will then be used to identify the outcome of the heart disease after the data has been useful.